The Polyamine Analogue Ivospemin Increases Chemotherapeutic Efficacy in Murine Ovarian Cancer - Cassandra E. Holbert; Jackson R. Foley; Robert A. Casero; Tracy Murray Stewart (Biomedicines, 2024)
Polyamines are small polycationic alkylamines that are absolutely required for the continual growth and proliferation of cancer cells. The polyamine analogue ivospemin, also known as SBP-101, has shown efficacy in slowing pancreatic and ovarian tumor progression in vitro and in vivo and has demonstrated encouraging results in early pancreatic cancer clinical trials. We sought to determine if ivospemin was a viable treatment option for the under-served platinum-resistant ovarian cancer patient population by testing its efficacy in combination with commonly used chemotherapeutics. We treated four ovarian adenocarcinoma cell lines in vitro and found that each was sensitive to ivospemin regardless of cisplatin sensitivity. Next, we treated patients with ivospemin in combination with four commonly used chemotherapeutics and found that ivospemin increased the toxicity of each; however, only gemcitabine and topotecan combination treatments were more effective than ivospemin alone. Using the VDID8+ murine ovarian cancer model, we found that the addition of ivospemin to either topotecan or gemcitabine increased median survival over untreated animals alone, delayed tumor progression, and decreased the overall tumor burden. Our results indicate that the combination of ivospemin and chemotherapy is a worthwhile treatment option to further explore clinically in ovarian cancer.